2017
DOI: 10.4103/0970-0218.199792
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of depression in community-dwelling elderly in rural Haryana, India

Abstract: Background:Depression in the elderly has been emerged as a serious public health challenge in the developing countries. Elderly population with depression is on rise in India, but is not adequately addressed. This study was planned to ascertain the prevalence of depression among elderly in a rural population of Haryana and assess its socio-demographic correlates.Methods:This study was a community based, cross sectional study, which was conducted in Community Health Centre (CHC), Chiri of Rohtak district (Harya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
36
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 27 publications
8
36
1
Order By: Relevance
“…In the present study, a significantly higher proportion of women suffered from depression compared with men ( p <0.001), which agrees with the results of studies conducted in many countries. 1 , 10 , 18 , 19 , 32 As a fact of life, the female sex has a high tendency to develop depression. For elderly women, the underlying reasons are being old, being women, and being poor; moreover, they are mostly deprived of family support, especially after an early loss of their spouses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, a significantly higher proportion of women suffered from depression compared with men ( p <0.001), which agrees with the results of studies conducted in many countries. 1 , 10 , 18 , 19 , 32 As a fact of life, the female sex has a high tendency to develop depression. For elderly women, the underlying reasons are being old, being women, and being poor; moreover, they are mostly deprived of family support, especially after an early loss of their spouses.…”
Section: Discussionmentioning
confidence: 99%
“…For elderly women, the underlying reasons are being old, being women, and being poor; moreover, they are mostly deprived of family support, especially after an early loss of their spouses. 18 , 19…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference was found statistically significant for hypertension, diabetes mellitus and neurological disorders. (Table 4) In a population based study by Pilania et al (2017) in Haryana showed prevalence of depression to be higher in study participants with chronic morbidity (20.9%) as compared to those who had no chronic morbidity (6.9%) and this difference was found statistically significant for diseases like diabetes (35.3%), hypertension (31%), respiratory disorders (23.3%) and hemiparesis (12.8%). (11) Mukeshimana and Mchunu (2016) in a review of articles published from 1991 to 2012 on comorbidity of Depression and other Chronic Noncommunicable Diseases found that the prevalence of depression was significantly higher in those with chronic non-communicable diseases in all regions of the world.…”
Section: Depression Prevalencementioning
confidence: 99%
“…A meta-analysis reported that the worldwide prevalence rate of depressive disorders in elderly population between 4.7% and 16% with a comparatively higher prevalence of 21.9% in India [2]. A study conducted in North India has shown that the prevalence of depression in the elderly was high even in a rural community with an estimate of 14.4% [3]. Hamilton Rating Scale for depression states that key features of depression include weight loss and reduced appetite [4].…”
Section: Introductionmentioning
confidence: 99%